The muon content of hybrid events recorded at the Pierre Auger Observatory - Farrar, Glennys R. (2014)
The hybrid events of the Pierre Auger Observatory are used to test the leading, LHC-tuned, hadronic interaction models. For each of 411 well-reconstructed hybrid events collected at the Auger Observatory withenergy 10E18.8 − 10E19.2 eV, simulated events with a matching longitudinal profile have been produced using QGSJET-II-04 and EPOS-LHC, for proton, He, N, and Fe primaries. The ground signals of simulated events have a factor 1.3-1.6 deficit of hadronically-produced muons relative to observed showers, depending on which high energy event generator is used, and whether the composition mix is chosen to reproduce the observed Xmax distribution or a pure proton composition is assumed. The analysis allows for a possible overall rescaling of theenergy, which is found to lie within the systematic uncertainties.